Information Bulletin, 2 1974. - Council of Europe, Strasbourg (France). Documentation Center for Education in Europe; Council of Europe, Strasbourg (France). Documentation Center for Education in Europe ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
The Information Bulletin, which is distributed free of charge three times a year in an English and a French edition, describes the educational, cultural, and scientific activities of the Council of Europe and reprints important policy documents of European interest in these fields. This bulletin has two major sections. The first part reports the activities of the Council for Cultural Co-operation, and discusses higher education and research, general and technical education, out-of-school education, cultural development, and educational documentation and research. The second part includes the introductory address and papers delivered at the Colloquium of Directors of Educational Research Organizations, Paris, November 7-9, 1973. Several of the papers included discuss the researcher and his roles as an adviser to the educational policy maker, as an agent of educational innovation, and as an agent of innovation in the classroom. A report on the 1973 Survey of Educational Research Policy in European Countries, and conclusions and recommendations on the training and career structures of educational researchers concludes the second part. (Author/RM)
Educational level discussed: Higher Education.
Educational level discussed: Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Career Planning; Comparative Education; Educational Innovation; Educational Planning; Educational Policy; Educational Research; Educational Researchers; Educational Technology; Higher Education; International Education; International Programs; Lifelong Learning; Medical Education; Relevance (Education); Secondary Education; European Education; Journal Articles